MALAY’S MYSTIC RAIN RITUAL: THE INFLUENCE OF CULTURAL ATTITUDES OF RAIN-STOPPING RITUAL TOWARD RECOGNITION OF INDONESIAN CUSTOMARY AND LOCAL WISDOM AND ITS ISLAMIC PERSPECTIVE - Suroyo, Suroyo; Putra, Bima Maulana; Soedjiwo, Novena Ade Fredyarini; Soriente, Antonia Soriente; Reforyani, Endang (The Pontianak State Institute of Islamic Studies, 2025)
The phenomenon that occurred in the MotoGP event that took place in Mandalika stole the attention of the national and international public for the action of the rain handlers who were invited to the event. This research is descriptive qualitative research using interview instruments as a data collection tool, key informants taken using purposive sampling are individuals who have knowledge in the fields of cultural studies and anthropology, in addition, the criteria of key informants are individuals who have a description of the rain handler and never witnessed the process of stopping the rain. The results found explain that the rain handler ritual is not only found in Indonesia, but in various countries with certain callings, even so, there are many polemics and contra that occur in society that relate to certain religious aspects, however, cultural studies have also observed if The local wisdom of the rain handler has become part of Indonesia, because every region in Indonesia still maintains and is even still carrying out the process of stopping rain, this is also still true in some Malay areas such as Siak Regency. Thus, the cultural wealth that still survives should be part of the culture and must be preserved, so that the original Indonesian culture will not become extinct.